Phonoaudiological role in neurogenic dysphagia due to Alzheimer’s Disease (Research, Society and Development, 2024)
Introduction: Swallowing is a biological function characterized as the act of swallowing and involves the participation of several muscles that depend on neurological organization for the proper functioning of this function. Neurological disorders can affect the coordinated contraction of the muscles involved in swallowing and cause dysphagia, as in Alzheimer's Disease (AD), a dementia that can occur in individuals of pre-senile or senile age. Given that individuals with Alzheimer's disease may present with Oropharyngeal Dysphagia (OD), the speech therapist is the professional capable of rehabilitating this dysphagia in order to promote food safety and the patient's quality of life. The objective of this work is to analyze speech therapy in neurogenic dysphagia caused by Alzheimer's disease. Methods: This is an integrative review that covered four databases, where a critical reading and analysis of studies published in the period between 2016 and 2022 was conducted, with the descriptors “Alzheimer's Disease” and “Swallowing Disorders”, “Alzheimer Disease” and “Swallowing Disorders”, in Portuguese and English. Results: From eleven articles, all research evaluated the clinical signs of oropharyngeal dysphagia in Alzheimer's disease, three addressed the relationship between speech therapy and AD, three aspects of speech therapy assessment and six addressed the rehabilitation of patients. Conclusion: The present study analyzed speech therapy in oropharyngeal dysphagia due to Alzheimer's disease and showed that the speech therapist is the professional capable of evaluating and treating swallowing disorders.